Women Resistance in Drama Scripts Perempuan Salah Langkah by Wisran Hadi - Rizkiyah Afdhaliyah; Moza Shafira (Ikaprobsi, 2023)
Literary works are a tool to voice women's rights. The presence of literary works can be used as information for readers about the struggles of women's forms of resistance or resistance to the customs and culture that bind them. Wisran Hadi's drama